Gambaran Pengetahuan, Sikap Dan Perilaku Pentingnya APD Pada Tenaga Kesehatan Selama Pandemi Covid-19 - Shomadya Bayu Ifana; Silviana Tirtasari; Siufui Hendrawan (Journals of Ners Community, 2022)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2), which first appeared in Wuhan, China and was reported in December 2019. In early October 2021, it was reported According to the World Health Organization (WHO), there are approximately 233 million people in the world who have confirmed COVID-19, while the number of patients who died has been recorded at approximately 4 million people. This study was to describe the knowledge, attitudes, and behavior of the importance of PPE for health workers in hospitals. This research is a descriptive cross-sectional design. In this study, all health workers at Sunan Kudus Islamic Hospital who met the inclusion and exclusion criteria were 169 respondents. In the study, the average age of respondents was 35 years, 135 respondents (79.9%) were women and 34 respondents (20.1%) were men. The average length of work of respondents is 10 years, the longest working respondent is 30 years and the new one is 1 year. The majority who worked in the inpatient room were 109 respondents (64.5%), outpatient room 31 respondents (18%), intensive care room 8 respondents (4.7%), emergency room 21 respondents (12.4%). The picture of the majority of good knowledge on the importance of PPE 168 respondents (99.4%), less good one respondent (0.6%), good attitude towards the importance of PPE 167 respondents (98.8%), bad attitude 2 respondents (1,2 %), good behavior on the importance of PPE 167 respondents (98.8%), bad behavior 2 respondents (1.2%). Health workers have good knowledge, attitude and behavior overall about the importance of PPE